162 WNT5a INHIBITS THE CANONICAL PATHWAY. (1st January 2006) - Villosis, M. F.B.; Hu, L. Y.; Li, C.; Minoo, P.
Abstract : A major signaling pathway in mammalian development is WNT. Binding of the WNT ligands to their receptors known as Frizzled (Fzd) results in activation of at least two intracellular pathways. The "canonical" pathway controls cell-fate determination and is mediated through stabilization of beta-catenin and activation of the lymphoid enhancer-binding factor/T cell factor (Lef/Tcf) through which gene expression is regulated. The "noncanonical" pathway is mediated by signaling through protein kinase C (PKC). WNT5a is a member of WNT family of proteins whose overexpression leads to lung immaturity. Repression of this gene results in postnatal demise. WNT5a can signal via the noncanonical pathway, but its role on the canonical pathway remains unclear. To determine the effect of WNT5a on the canonical pathway, we generated double transgenic mice, SPC:Wnt5a;TOP-Gal, and studied the expression of LacZ from the Top-Gal promoter. In the lungs of these double transgenic mice, LacZ expression is reduced compared to that of single transgenic TOP-Gal mice, suggesting inhibition of the canonical pathway by WNT5a. To further substantiate the latter in vivo findings, we conducted transfection studies in the human lung carcinoma, A549 cells, using the canonical-WNT-signaling reporter construct TopFlash. TopFlash was co-transfected with expression construct for either Wnt3a, Wnt5a, or both and analyzed using luciferase assay. The results demonstrate that Wnt5a attenuates the activation of TopFlash by Wnt3a. In summary, both in vivo and in vitro results are consistent with the conclusion that WNT5a inhibits the canonical WNT signaling pathway. Supported by the Hastings Foundation, HL56590 and HL073471.